Adenylate Cyclase Toxin Tinkering With Monocyte-Macrophage Differentiation - Ahmad, Jawid Nazir; Sebo, Peter (Frontiers in immunology, 2020)
Circulating inflammatory monocytes are attracted to infected mucosa and differentiate into macrophage or dendritic cells endowed with enhanced bactericidal and antigen presenting capacities. In this brief Perspective we discuss the newly emerging insight into how the cAMP signaling capacity of Bordetella pertussis adenylate cyclase toxin manipulates the differentiation of monocytes and trigger dedifferentiation of the alveolar macrophages to facilitate bacterial colonization of human airways.
Keywords: dediferenciace buněk; dýchací soustava; Immunity, Mucosal; Animals; systémy druhého messengeru; biologické modely; AMP cyklický; alveolární makrofágy; přirozená imunita; Second Messenger Systems; dedifferentiation; adenylate cyclase toxin; prezentace antigenu; Adenylate Cyclase Toxin; Bordetella pertussis; buněčná diferenciace; lidé; Models, Biological; Mice; monocyty; myši; Macrophages, Alveolar; Cyclic AMP; Monocytes; fagocytóza; Immunity, Innate; Phagocytosis; interakce hostitele a patogenu; Cell Differentiation; macrophages; zvířata; Cell Dedifferentiation; Host-Pathogen Interactions; monocytes; slizniční imunita; Antigen Presentation; adenylátcyklasový toxin; Respiratory System; Humans